2015
DOI: 10.1186/s12974-015-0318-4
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a distinct neuro-immune signature in rats that develop behavioural disability after nerve injury

Abstract: BackgroundChronic neuropathic pain is a neuro-immune disorder, characterised by allodynia, hyperalgesia and spontaneous pain, as well as debilitating affective-motivational disturbances (e.g., reduced social interactions, sleep-wake cycle disruption, anhedonia, and depression). The role of the immune system in altered sensation following nerve injury is well documented. However, its role in the development of affective-motivational disturbances remains largely unknown. Here, we aimed to characterise changes in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
32
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(45 citation statements)
references
References 88 publications
(100 reference statements)
10
32
1
Order By: Relevance
“…The previous clinical studies demonstrated that the incidence of comorbid chronic pain and depression is around 30-50% [1,4,5], which is in line with the present study. In this study, we found that rats with or without anhedonia-like phenotypes showed similar mechanical withdrawal thresholds, suggesting that the alterations in mood-related behaviors were independent of the degree of nociceptive damage, consistent with the previous studies [8,31,[38][39][40].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The previous clinical studies demonstrated that the incidence of comorbid chronic pain and depression is around 30-50% [1,4,5], which is in line with the present study. In this study, we found that rats with or without anhedonia-like phenotypes showed similar mechanical withdrawal thresholds, suggesting that the alterations in mood-related behaviors were independent of the degree of nociceptive damage, consistent with the previous studies [8,31,[38][39][40].…”
Section: Discussionsupporting
confidence: 92%
“…In preclinical studies, rats with hyperalgesia were highly heterogeneous in depression-related behaviors. Keay and colleagues reported that chronic constriction injury (CCI) induced a subgroup (approximately 30%) of rats that had altered dominant behavior [8] and sleep-wake cycles [38] using resident-intruder social interaction and sleep-wake analyses. In this study, the hierarchical cluster analysis divided SNI rats into two clusters: one group (approximately 40%, 'anhedonia-like phenotype') with reduced sucrose preference in the SPT, the other group (approximately 60%, 'without anhedonia-like phenotype') with similar sucrose preference compared with sham-operated rats.…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12][13] However, substantial evidence has been accumulating, particularly in models of peripheral neuropathies, suggesting that hypersensitivity and the behavioral impairments can to a certain extent dissociate. [15][16][17][18][19][20][21][22][23] Also, previous studies from our group showed that left-and right-sided injuries are differentially associated with specific behavioral deficits, but no differences were observed in their algogenic quality. The proportion of affected animals was shown to be constant and associated with particular morphological, endocrine, inflammatory and genetic outcomes.…”
Section: Introductionmentioning
confidence: 60%
“…CCL2, CCL3, CCL5, IL-1β, and IL-6 are upregulated in damaged nerves, DRGs, and spinal cord dorsal horn (6063) in variety of models and neuropathic pain is decreased by antagonists, neutralizing antibodies, microglia inhibitors, or in CCL2 deficient mice (62, 6466). However, in the present study, CCL3 expression was elevated at all ages at PS1 in the root compression and at PS7 in the nerve compression injury, which is not consistent with the appearance of thermal or mechanical hyperalgesia.…”
Section: Discussionmentioning
confidence: 99%